Experimental investigation on DMFCs using reduced noble metal loading with NiTiO3 as supportive material to enhance cell performances. (21st May 2019) - Thiagarajan, V.; Karthikeyan, P.; Thanarajan, K.; Neelakrishnan, S.; Manoharan, R.; Chen, Rui; Fly, Ashley; Anand, R.; Karuppa Raj, Thundil R.; Sendhil Kumar, N.
Abstract: In this present work, the effect of anode electrocatalyst materials is investigated by adding NiTiO3 with Pt/C and Pt-Ru/C for the performance enhancement of direct methanol fuel cells (DMFCs). The supportive material NiTiO3 /C has been synthesized first by wet chemical method followed by incorporation of Pt and Pt-Ru separately. Experiments are conducted with the combination of four different electrocatalyst materials on the anode side (Pt/C, Pt-NiTiO3 /C, PtRu/C, Pt-Ru-NiTiO3 /C) and with commercial 20 wt % Pt/C on the cathode side; 0.5 mgpt /cm 2 loading is maintained on both sides. The performance tests of the above catalysts are conducted on 5 cm 2 active area with various operating conditions like cell operating temperatures, methanol/water molar concentrations and reactant flow rates. Best performing operating conditions have been optimized. The maximum peak power densities attained are 13.30 mW/cm 2 (26.6 mW/mgpt ) and 14.60 mW/cm 2 (29.2 mW/mgpt ) for Pt-NiTiO3 /C and Pt-Ru-NiTiO3 /C at 80 °C, respectively, with 0.5 M concentration of methanol and fuel flow rate of 3 ml/min (anode) and oxygen flow rate of 100 ml/min (cathode). Besides, 5 h short term stability tests have been conducted for PtRu/C and Pt-NiTiO3 /C. The overall results suggest that the incorporation of NiTiO3 /C supportive material to Pt and Pt-Ru appears to make a promising anode electrocatalysts for the enhanced DMFC performances. Highlights: Nanostructured anode electro-catalysts of Pt-NiTiO3 /C and Pt-Ru-NiTiO3 /C has been synthesized. Performance evaluation for anode electro-catalysts on 5 cm 2 DMFC and compared with Pt/C and PtRu/C. Pt-NiTiO3 /C and Pt-Ru-NiTiO3 /C shows better performance at low loading of Pt (0.5 mgPt /cm 2 ). Stability analysis is carried out for 5 h on Pt-NiTiO3 /C and results are analysed.